Cooperation in Eurasia Linking Identity, Security, and Development - Carlo Frappi (Pubblicazioni ISPI, 2018)
Result of a joint research project conducted by the Institute for International Political Studies (ISPI) and the Center for Strategic Studies under the President of the Republic of Azerbaijan (SAM), the volume "Cooperation in Eurasia: Linking Identity, Security, and Development" aims to shed light on the drivers and on the rationale behind regional cooperation in Eurasia. In particular it investigates and ponder the weight of identity issues, security perceptions, and economic development needs for interstate cooperation in the Eurasian context, by taking into account both supra-national frameworks and regional scenarios. Accordingly, the book is divided in two parts, focusing respectively on "Cooperation and Competition at Multilateral Level" and on "Regional Case Studies".